A Framework for Secondary School Education Portal - Siti Nazuar, Sailin (2004)

(untitled)
The purpose of this research is to utilize Information Technology (IT) facilities and infrastructure to facilitate the teaching and learning system in Malaysia. This research aims to introduce an education portal framework as an online learning platform for secondary schools in Malaysia. The methodology applied in this research is Action Research method that includes data gathering process using case study and Expert Review technique. The framework develop from this research was established based on the identification of the key features and functions of an education portal system as put forward by previous researches and added features and functions as recommended by IT and education experts. The framework was transformed into prototype system and tested among selected respondents to assess the perceptions of pupils and teachers on the prototype being developed. The study found that education portal framework is crucial to the Malaysian teaching and learning system in order to implement an online learning environment in schools. Pupils and teachers also agreed that the education portal is important to assist the teaching and learning system. Furthermore, in line with the reigning wired teaching and learning environment in the Malaysian education system, the education portal framework is crucial in achieving the goal of online education in Malaysia. Thus, it is hoped that the framework established from this research can be used as a guide in planning and developing education portal solution.